Hepatitis C virus as possible etiologic factor in idiopathic nephrotic syndrome among Egyptian patients - Sally, Samir M; Khalil, Fawzy M; Negm, Shareif (African Journal of Nephrology, 2016)
Hepatitis C virus (HCY) infection is associated with a variety of extrahepatic disorders. including cryoglobulinaernia and glomerulonephritis. Hepatitis C virus (HCV) glornerulopathy may be present as a primary glomerular disease. Our study included 50 adult Egyptian patients who were diagnosed as idiopathic nephrotic syndrome (NS). We described the clinical, pathological and immunological features of these patients. There was a high prevalence (50%) of HCV infection among these patients. The studied risk factors included history of; blood transfusion (16%) operation (24%) or antibilharzial drugs (76%). Hepatomegaly was observed in 24% of cases. Mernbranoproliferative glomerulonephritis (MPGN) was the commonest pathological type associated with HCV (48%). Other patterns included focal segmental glomerulosclerosis (FSGS) in 32%, membranous in 8% and minimal change glomerulonephritis in 12%. Cryoglobulins were detected in 5.6% of 18 patients with HCV and idiopathic NS. Patients having HCV infection and membranoproliferative glomerulonephritis had hypocomplementemia and antinuclear antibodies were detected in 41.6%. Realising that HCV infection may be linked to different glomerulopathies, thus routine screening for HCV should be considered in serologic work-up of patients with glomerulopathy. Nevertheless, seroepiderniological studies including larger number of patients with glornerulopathy are therefore necessary to specify its relation with HCV infection.